The importance of trasologi objects in criminology (Journal of actual problems of jurisprudence, 2019)
The criminalistic peculiarities of trassologi objects are considered in this article necessary are also drawn. Basic objectsof research of trasologii: statistical, dynamic. The general rules of finding, assertions and taking of tracks, are resulted.Strengthening of tracks is carried out description in protocol of consequence actions. A role and features of objects oftrassologii was scalene examined in scientific criminalistics.Key words: trasologii, dynamic tracks, local tracks, peripheral tracks, static tracks.